Temporal alteration of microglia to microinfarcts in rat brain induced by the vascular occlusion with fluorescent microspheres - Shen, Yi; Cui, Jingjing; Zhang, Shuang; Wang, Yuqing; Wang, Jia; Su, Yuxin; Xu, Dongsheng; Liu, Yihan; Guo, Yating; Bai, Wanzhu (Frontiers in Cellular Neuroscience, 2022)
Microglia, the resident immune cells in the central nervous system, can monitor the microenvironment and actively respond to ischemic stroke and other brain injuries. In this procedure, microglia and neurons can cross-talk via transmembrane chemokine, Fractalkine (CX3CL1) to impact one another. We used a rat model of multifocal microinfarcts induced by the injection of fluorescent microspheres into the right common carotid artery, and examined the morphological alteration of blood vessels, microglia, astrocytes, and neurons at 6 hours, 1 day, 7 days and 14 days after modeling, along with neurobehavioral tests and the staining of CX3CL1 in this study. Our results demonstrated that in the infarcted regions, astrocytes and microglia activated in response to neuronal degeneration and up-regulation of cleaved caspase- 3, which occurred concurrently with vascular alteration and higher expression of CX3CL1. We provided sequential histological data to shed light on the morphological changes after modeling, which would help in the identification of new targets and the choice of the ideal time-window for therapeutic intervention in ischemic stroke.